Efficacy and safety of natural killer cell therapy in patients with solid tumors: a systematic review and meta-analysis - Park, Heesook; Kim, Gyurin; Kim, Najin; Ha, Sungyoen; Yim, Hyeonwoo (Frontiers in Immunology, 2024)
Introduction In 2020, global cancer statistics reported 19.3 million new cases and 10 million deaths annually, highlighting the urgent need for effective treatments. Current therapies, such as surgery, radiation, and chemotherapy, have limitations in comprehensively addressing solid tumor. Recent advances in cancer biology and immuno-oncology, including CAR-T cell therapy, show promise but face efficacy challenges against solid tumors. Methods This meta-analysis systematically reviewed studies from PubMed, Embase, Cochrane, and ClinicalTrials.gov databases up to May 2024 to evaluate the clinical efficacy and safety of unmodified NK cell therapies in solid tumors. The included trials focused on reporting objective response rates (ORR). Results Thirty-one trials involving 600 patients across various cancers (e.g., NSCLC, HCC, breast, ovarian) were analyzed. NK cell therapies demonstrated promising ORRs, particularly 72.3% in hepatocellular carcinoma, often in combination with local therapies. Safety profiles were favorable, with fatigue being the most common adverse event. Discussion NK cell therapies represent a promising treatment option for solid tumors, offering a viable alternative to genetically modified cell therapies like CAR-T. Further research is needed to optimize the clinical utility of NK cell therapy and integrate it effectively into standard cancer treatment regimens. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023438410, identifier CRD42023438410.